'Just because' Constructions in Spoken and Written New Zealand English - Andreea Calude; Gerald Delahunty (Journal of Linguistics and Language Teaching)
Just because (JB) is widely used and has been a target of commentary and humorous use by English speakers and aroused some interest among linguists, who have investigated its syntax, semantics, and derivation. Some, based on researcher constructed data, have proposed construction analyses (Hirose 1991, Bender and Kathol 2001). Another (Hilpert 2005: 97), using a diachronic corpus, proposes that JB has been grammaticalized as a concessive marker via "the discourse function of inference denial." Our study, based on a corpus of New Zealand written and spoken English, demonstrates, amongst other significant findings, that JB occurs in a far broader set of grammatical contexts than the earlier literature recognizes, that JB constructions are significantly more frequent in spoken than in written English, that JB adverbial clauses are more likely to occur in pre-posed than in post-posed position, that the meaning of just because affects this distribution, that just because is far more likely to be followed by a clause than a prepositional phrase, and that JB constructions are extremely likely to occur in the discourse context of a negator.